KUNCI KESUKSESAN IMPELEMENTASI BALANCED SCORECARD DI INDONESIA - Tanios, Debby; Alamsjah, Firdaus (Journal of Business Strategy and Execution, 2009)
In this era, a very competitive business environment and turbulance have encouraged companies to measure their performance in planning goals in the future. Without measurement, a company will never know whether a correct strategy has been implemented or whether the strategy has been well implemented. Therefore, there exist several performance measurement systems. In the last decade, the Balanced Scorecard (BSC) is one of most succesfull concepts and has become the top-list tool for performance measurement system in the world. Many companies has claimed that they adopted BSC but some of them were not continously used because they were assumed not being able to give a significant contribute to the business development. The purpose of this research is to find which factors influenced the successful of BSC’s implementation, so that business practitioners may focus on the success factors. By collecting data using questionnaire and using the SPSS software to utilise Chi-Square and multiple regression methods for the data analysis, the transition time, scorecard design, scorecard’s detail distribution to all levels, BSC development process time, and treat BSC as a project system have given a significant influence toward the success of BSC implementation.